An Experimental Investigation of FRCC Shear Walls Reinforced with Steel and GFRP Bars - Mohammad J. Tolou Kian (Journal of Composites Science, 2018)
Contemporary structures can resist earthquakes as they deform and dissipate energy. However, during strong ground motions, these structures can sustain significant concrete damage and overall permanent deformations. Therefore, it is of great benefit if earthquake-resisting structures can deform and dissipate energy, and yet sustain mitigated damage. This paper illustrates the findings of an experimental study focused on the mitigation of damage and reduction of residual displacements in reinforced concrete (RC) shear walls. In this study, the cyclic properties of two innovative shear walls—a slender and a squat wall—which were cast with fiber-reinforced cementitious composites and reinforced with steel and glass fiber reinforced polymer bars are investigated. Then, the improvements of the innovative specimens with respect to two conventional RC shear walls are discussed in terms of damage propagation, self-centering, stiffness retention and energy dissipation. As the experiments showed, the innovative walls sustained mitigated concrete damage and less residual drift ratios while illustrating significant stiffness and energy dissipation capacities.